Occurrence, distribution, and ecotoxicological risk assessment of selected pharmaceutical compounds in water from Lake Victoria, Uganda - Nantaba, Florence; Wasswa, John; Kylin, Henrik; Palm, Wolf-Ulrich; Bouwman, Hindrik; Kümmerer, Klaus (Chemosphere, 2020)
The occurrence of 24 pharmaceuticals (including; 15 antibiotics, three analgesic/anti-inflammatory drugs, three anti-epileptic/ antidepressant drugs, two beta blockers, and one lipid regulator) was investigated in 75 water samples collected from four bays in the Ugandan part of Lake Victoria. In addition, the potential environmental risk of the target pharmaceutical compounds to aquatic organisms in the aquatic ecosystem of Lake Victoria was assessed. Water samples were extracted using solid phase extraction and analyzed for pharmaceuticals using high- performance liquid chromatography coupled with triple quadrupole mass spectrometry (LC/MS/MS). Eighteen of the 24 pharmaceuticals occurred at quantifiable concentrations. Sulfamethoxazole (1-5600 ng L-1), trimethoprim (1-89 ng L-1), tetracycline (3-70 ng L-1), sulfacetamide (1-13 ng L-1), and ibuprofen (6-780 ng L-1) occurred at quantifiable concentrations in all water samples. Sulfamethazine (2-50 ng L-1), erythromycin (10-66 ng L-1), diclofenac (2-160 ng L-1), and carbamazepine (5-72 ng L-1) were only quantifiable in water samples from Murchison Bay. The highest concentrations of pharmaceuticals were found in Murchison Bay, the main recipient of sewage effluents, industrial and municipal waste from Kampala city via the Nakivubo channel. Ecotoxicological risk assessment showed that sulfamethoxazole, oxytetracycline, erythromycin, and diclofenac pose a high toxic risk to aquatic organisms in the lake, while ciprofloxacin, norfloxacin, and ibuprofen pose a medium risk. This study is the first of its kind to report the levels and ecotoxic risks of pharmaceutical compounds in Lake Victoria waters, of Uganda, and East Africa as a whole.
Keywords: Pharmaceuticals; Risk assessment; Lake Victoria; Surface water; East Africa